Characterizing 4C Skills of Pre-Service Chemistry Teachers Through Inquiry-Based Learning with Multiple Representations (IBL-MR): Rasch Model Analysis - Mardhiya, Julia; Setiowati, Hanifah; Putri, Ananda Erika (Pendidikan Kimia FKIP Universitas Jambi, 2025)
21st century education requires the development of 4C skills, namely critical thinking, communication, collaboration, and creativity, especially for prospective chemistry teachers. The purpose of this study was to be characterizing the profile of students' 4C skills after participating in the Inquiry-Based Learning Multiple Representation (IBL-MR) model designed to promote deep learning. The IBL-MR model emphasizes conceptual understanding through scientific inquiry activities and the integration of multiple representations into chemistry instruction. The subjects of the study were 30 first-year students in the chemistry teacher education program at UIN Walisongo Semarang, selected using a purposive sampling technique. This instrument was developed based on the 4C skill indicators that were valid and reliable. Analysis of the profile of pre-service chemistry using the Rasch model with Winsteps software. The results showed that collaboration skills had the highest achievement (+0.54 logit), followed by critical thinking (+0.32 logit) and communication (+0.12 logit), while creative thinking showed the lowest achievement (–0.18 logit). Wright Map analysis and person-item fit also showed significant variation in ability between individuals. These findings indicate that the IBL-MR strategy is effective in developing most of the 4C skills, but specific reinforcement for creative thinking and communication aspects is still needed through more exploratory and reflective pedagogical interventions. Keywords: 4C skills; critical thinking; communication; collaboration; creativity; inquiry-based learning multiple representations; deep learning